Formas de la dominación social en las ficciones alegóricas y metafóricas realizadas en épocas de la dictadura y la postdictadura en Argentina - Ana Laura Lusnich (IdeAs)
During last Argentine militar dictatorship (1976-1983), and first period of the post-dictatorship (1983-1989), the hermetic-metaphoric fictions constituted an alternative cinematographic tendency that showed the main conflicts of that time in a reflexive and critical way. The construction of opaque tales that evading the realistic-mimetic representation and the primacy of the allegorical and metaphorical operations as constructive principles were two textual features that gave uniqueness to the trend.  With the intention of knowing the permeability of this cinematographic line in respect of the political practices and the situations of terror imposed in the years of non-constitutional governments, the present work proposes to analyze the representation of the domination against individuals and the society, with emphasis in the emplacements and/or the displacements of dramatical subjects and the reference to situations of internal and external exile. The second objective of the paper includes the identification, in these historical situations associated to discipline and social extreme control, of subjectivities characterized by fracture and instability. The development of both aspects will be focused on two outstanding films of the trend: Los miedos [“Fears”] (Alejandro Doria, 1980) and Hay unos tipos abajo [“Some guys downstairs”] (Rafael Filippelli and Emilio Alfaro, 1985).